USULAN PENGENDALIAN KUALITAS UNTUK MENGURANGI PRODUK CACAT KEMASAN MINYAK TELON - Hesti Puspitasari; Joko Susetyo; Rahayu Khasanah (Jurnal Rekavasi, 2022)
ABSTRACT PT. Aksamala Adi Andana is a company that produces health products, one of which is "Habbie" telon oil. The increasing demand for products requires companies to maintain and improve the quality of their products. But there are still many defective products that are not in accordance with the standards set by the company. The percentage of telon oil product packaging defects in the January 2020 - December 2020 period reached 5.26%, exceeding the defect tolerance limit of 2%. Types of defects in telon oil product packaging include label sticker defects, cap defects, bottle defects, and folding box defects. Based on the analysis using the Statistical Quality Control (SQC) method, the results of the Pareto diagram show the order of the percentage causes of telon oil product packaging defects, namely sticker label defects (55%), cap defects (21%), bottle defects (13%), and folding box defects. (11%), and the results of the p control chart show that there are 7 of the 12 period points that are outside the control limits with a value of Cp = 0.9489. Based on the analysis using the Failure Mode And Effect Analysis (FMEA) method, the highest RPN value is 192 for the sticker label defect. The Kaizen method is used to generate proposed corrective actions for factors causing defects with the aim of reducing defective products.